The Function and Symbolic Meaning of Pinar Uloni Horbo, the Bolon House of the Simalungun Batak Ethnic Group: A Semiotic Study: - Roma Hotni Uhur Purba; Immanuel Silaban; Bunga Sarido N. Manullang; Ridho Wahyu C. Silaban (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Rumah Bolon Pematang Purba is a traditional house that is a legacy of the Simalungun kingdom that keeps the cultural values and philosophy of its people’s lives. One of the most prominent elements in this building is the uluni horbo ornament, which is an ornament that resembles a buffalo head or horn located on the ridge of the roof of the house. This ornament not only functions as a decorative element, but also loaded with symbolic meanings that reflect the belief system and view of life of the Simalungun people. This research aims to examine the function and meaning of uluni horbo ornaments in the Bolon Pematang Purba House by using a semiotic approach. The research method used is qualitative descriptive through field observation, interviews with traditional figures, visual documentation, and literature analysis related to architecture and Simalungun cultural symbols. Research results show that uluni horbo ornaments have a social and religious function, namely as a symbol of power and king status, protection against the influence of evil spirits, as well as a representation of the value of courage, strength, and human harmony with nature and ancestors. In the framework of semiotics, uluni horbo plays a role as a visual sign (marker) that has a sign in the form of the meaning of power, legitimacy, and cultural identity. This study confirms that the ornaments in the Simalungun traditional house cannot be separated from the symbolic system of its community, because every shape and position has a meaning that connects aesthetic, spiritual, and social aspects. Thus, the preservation of ornaments such as uluni horbo becomes important to maintain the continuity of cultural values and ethnic identity of Simalungun.